Foot plantar pressure measurement system using highly sensitive crack-based sensor - Park, Jieun; Kim, Minho; Hong, Insic; Kim, Taewi; Lee, Eunhan; Kim, Eun A.; Ryu, Jae Kwan; Jo, Yongjin; Koo, Jeehoon; Han, Seungyong; Koh, Je Sung; Kang, Daeshik (Sensors (Switzerland), 2019)
Measuring the foot plantar pressure has the potential to be an important tool in many areas such as enhancing sports performance, diagnosing diseases, and rehabilitation. In general, the plantar pressure sensor should have robustness, durability, and high repeatability, as it should measure the pressure due to body weight. Here, we present a novel insole foot plantar pressure sensor using a highly sensitive crack-based strain sensor. The sensor is made of elastomer, stainless steel, a crack-based sensor, and a 3D-printed frame. Insoles are made of elastomer with Shore A 40, which is used as part of the sensor, to distribute the load to the sensor. The 3D-printed frame and stainless steel prevent breakage of the crack-based sensor and enable elastic behavior. The sensor response is highly repeatable and shows excellent durability even after 20,000 cycles. We show that the insole pressure sensor can be used as a real-time monitoring system using the pressure visualization program.
Keywords: Elastic behavior; Foot plantar pressures; Plantar pressure sensors; Pressure measurement system; Real time monitoring system; Sensor response; Sports performance; Strain sensors; Equipment Design; Foot Orthoses; Gait; Humans; Models, Theoretical; Pressure; Printing, Three-Dimensional; Crack-based sensor; Foot plantar pressure; Insole pressure sensor; Pressure measurement system